Rarefaction effects on the flow characteristics in microchannels on asymmetric wall thermal condition - Islam, Md. Tajul (International Journal of Applied Mathematical Research, 2015)
Rarefaction effects on the flow characteristics in 2D microchannels on asymmetric wall thermal conditions are investigated by control volume technique. In order to examine the influence of Knudsen numbers on the flow characteristics, a series of simulations for both compressible and incompressible flow with different Reynolds and Knudsen numbers are performed. Nitrogen gas is used as working fluid and the slip boundary conditions are used on the walls. The Navier-Stokes and energy equations are solved simultaneously. The results are found in good agreement with those predicted by analytical solutions in 2D continuous flow model employing first order slip boundary conditions. It is shown here that the Knudsen number has effects on velocity and temperature distribution for both the compressible and incompressible flows. It causes the velocity slip on the wall and causes the temperature difference between the wall temperature and the gas temperature on the wall.